Angiosarcoma of the Breast: Management and Outcomes. (November 2020) - Gutkin, Paulina M.; Ganjoo, Kristen N.; Lohman, Marti; von Eyben, Rie; Charville, Gregory W.; Nazerali, Rahim S.; Dirbas, Frederick M.; Horst, Kathleen C.
Abstract : Objective: Angiosarcoma of the breast is rare and has a poor prognosis. We reviewed our institution's experience with this disease to characterize presentation, identify management patterns, and report outcomes. Methods: Fifty-eight patients with nonmetastatic angiosarcoma were identified from 1998 to 2019 and retrospectively reviewed. Overall survival (OS) and recurrence-free survival (RFS) were calculated using the Kaplan-Meier analysis and log-rank test. Results: The median follow-up was 43.4 months (range: 1.8 to 203.3 mo). Twenty-four patients had primary angiosarcoma (PAS) and 34 patients had secondary angiosarcoma (SAS). Patients with PAS were significantly younger than those with SAS ( P <0.0001). Mastectomy was the main surgical treatment in our cohort (n=47) and 3 underwent a lumpectomy. The multifocal disease was found in 5/23 patients with PAS and 11/35 patients with SAS. Twenty-eight patients received chemotherapy. Radiation was administered to 13 patients with PAS and 3 patients with SAS. Five-year OS was 73.7% for PAS and 63.5% for SAS. Local recurrence occurred in a greater proportion of patients with margins <5 mm than those with margins ≥5 mm. Chemotherapy did not impact RFS and was not associated with OS in PAS ( P =0.35). Those with SAS treated with chemotherapy had significantly greater OS than those who did not receive chemotherapy ( P =0.043). Radiation did not significantly influence RFS or OS. Conclusions: Five-year OS was higher than anticipated. Margins >5 mm appear important for local control. Patients with SAS, but not PAS, may achieve improved survival with chemotherapy. National trials using prespecified agents may be needed to identify an optimal chemotherapy regimen for women with SAS.